Ejawi converter mobile application - Nur Azie Hazmida, Binti Abdul Hazis (Universiti Malaysia Sarawak (UNIMAS), 2017)
Ever since Roman alphabets were introduced to replace the traditional Jawi script in Tanah Melayu, the interest in Jawi amongst the local has significantly dwindled. If no preservation scheme is taken, it may disappear into extinction. Nonetheless, over the year, various initiatives are developed in order to protect and popularise the script to younger generation. From computer word processor, Jawi keyboard, Jawi-Rumi converters, reading materials, games, text recognition researches to mobile applications, these endeavours will continue to uphold the tradition to younger generation. In this project, these undertakings in terms of digitising the script are discussed, and mobile applications related to Jawi available in the market are analysed and compared. Subsequently, a new mobile application that is able to convert Rumi to its equivalent Jawi spelling, either by manual search or by exploiting text recognition from images technique is designed and developed. Database system, Java programming language and Optical Character Recognition (OCR) method are analysed and studied throughout the development of the mobile application.